(untitled) (The Review of Diabetic Studies, 2013)
Dyslipidemia is a major risk factor for cardiovascular complications in people with diabetes. Lowering low-density lipoprotein cholesterol (LDL-C) levels is effective in the primary and secondary prevention of diabetic vascular complications. However, LDL-C levels do not reflect all aspects of diabetic dyslipidemia, which is characterized by hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C). Statins, nicotinic acid, and fibrates play a role in treating diabetic dyslipidemia. Atherosclerosis is a major disorder of the blood vessel wall in patients with diabetes. A number of antihyperlipidemic agents may be beneficial and exhibit effects at the actual site of vascular disease and not only on plasma lipoprotein concentrations. Several novel therapeutic compounds are currently being developed. These include additional therapeutics for LDL-C, triglycerides, HDL-C, and modulators of inflammation that can be used as possible synergic agents for the treatment of atherosclerosis and irregularities in plasma lipoprotein concentrations.